PELATIHAN ECOPRINT SEBAGAI UPAYA MENGENALKAN KEWIRAUSAHAAN DI BIDANG EKONOMI KREATIF - Tasera, Yesi; Muslim, Muhammad Rifa’at Rifa’I; Jabar, Mochammad Reki Abdul; Darusman, Yus (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Indonesia is currently experiencing a demographic bonus, where the majority of the population is in the productive age range, around 70% of the total population , aged between 15 to 64 years. This data is a good opportunity as well as a challenge for the availability of jobs. One that can maintain the availability of jobs is entrepreneurship. Because entrepreneurship is one of the activities that can be done to work and open up job opportunities. With these technological advances, the world of entrepreneurship is also developing which is called the Creative Economy . One example of entrepreneurship in the field of creative economy is ecoprint. The purpose of this study is to introduce entrepreneurship in the scope of the creative economy by carrying out ecoprint training. The implementation method used in this Ecoprint Training is using lectures, discussions and demonstration methods. The results of this training, of course, are not all fully able to fully understand what entrepreneurship and also the creative economy mean. However, in the implementation of this ecoprint training, all learning residents who were involved felt a high sense of enthusiasm in participating in this training and Understand how broad and useful entrepreneurs in the creative economy sector are today.